ANALISIS KESENJANGAN PADA PELAYANAN PENDAFTARAN TANAH PERTAMA KALI DI KANTOR PERTANAHAN KOTA BEKASI - Sukirno, Nono; Mulyanto, Budi; Hakim, Dedi Budiman (Jurnal Ilmu Keluarga dan Konsumen, 2015)
In order to increase service performance of government agencies, the stakeholders have to pay attention to the satisfaction of the public it serves. This study aimed to determine the level of public satisfaction and further willbe analyzed the gap between service performances of the agency and public satisfaction to the service of Land Office of Bekasi City. This research was conducted at the Land Office of Bekasi City; held from March to June 2014. The design used in this study was a cross-sectional study. The samples were chosen by convenience sampling technique. Analysis of the gap was measured by Importance Performance Analysis (IPA). The results showed that the quality of land registration services that was provided by the Land Office of Bekasi City had not meet people's satisfaction. This was indicated by the difference between the average score of the service performance (3,22) and an the average score of the expectations (3,77). This finding showed a gap of -0,55 that means the service performance of the agency still lower that public expectation for the services. Moreover, punctuality was indicator that that had high gap score between the service performance and public satisfaction. Therefore, Land Office of Bekasi should have a policy to discipline its employees to be on time in service of land registration.